Managing airports an international perspective - Graham, Anne 1958- (Routledge/Taylor & Francis Group, 2023)
"Fully revised and updated to consider recent developments in the industry, the sixth edition of Managing Airports: An International Perspective provides comprehensive and cutting-edge insight into the processes behind running a successful airport. International and multi-disciplinary in approach, this edition is a vital resource for students, lecturers and researchers of transport and tourism, and practitioners within the air transport industry"--